Multimodal sequencing of neoadjuvant nivolumab treatment in hepatocellular carcinoma reveals cellular and molecular immune landscape for drug response - Fanhong Zeng; Qingyang Zhang; Yu-Man Tsui; Huanhuan Ma; Lu Tian; Abdullah Husain; Jingyi Lu; Joyce Man-Fong Lee; Vanilla Xin Zhang; Po-Man Li; Gary Cheuk-Hang Cheung; Tan-To Cheung; et al. (Molecular Cancer)
Abstract A striking characteristic of liver cancer is its extensive heterogeneity, particularly with regard to its varied response to immunotherapy. In this study, we employed multimodal sequencing approaches to explore the various aspects of neoadjuvant nivolumab treatment in liver cancer patients. We used spatially-resolved transcriptomics, single- and bulk-cell transcriptomics, and TCR clonotype analyses to examine the spatiotemporal dynamics of the effects of nivolumab. We observed a significantly higher clonal expansion of T cells in the tumors of patients who responded to the treatment, while lipid accumulation was detected in those of non-responders, likely due to inherent differences in lipid metabolic processes. Furthermore, we found a preferential enrichment of T cells, which was associated with a better drug response. Our results also indicate a functional antagonism between tumor-associated macrophages (TAMs) and CD8 cells and their spatial separation. Notably, we identified a UBASH3B/NR1I2/CEACAM1/HAVCR2 signaling axis, highlighting the intense communication among TAMs, tumor cells, and T-cells that leads to pro-tumorigenic outcomes resulting in poorer nivolumab response. In summary, using integrative multimodal sequencing investigations, combined with the multi-faceted exploration of pre- and post-treatment samples of neoadjuvant nivolumab-treated HCC patients, we identified useful mechanistic determinants of therapeutic response. We also reconstructed the spatiotemporal model that recapitulates the physiological restoration of T cell cytotoxicity by anti-PD1 blockade. Our findings could provide important biomarkers and explain the mechanistic basis differentiating the responders and non-responders.